The Singing Method and Its Impact on Arabic Vocabulary Acquisition Among Students at MTs Tarbiyah Islamiyah Batang Kabung - Hasibuan, Amarullah (Universitas Muhammadiyah Sumatera Barat, 2025)
This study addresses low motivation and mastery in Arabic vocabulary at MTs Tarbiyah Islamiyah Batang Kabung, where traditional rote memorization methods prevail. It investigates the singing method's impact, aiming to: 1) measure its effect on vocabulary mastery, 2) analyze its influence on motivation, and 3) evaluate its practical implementation. Employing a qualitative case study, data was gathered through classroom observations, in-depth interviews with teachers and students, and document analysis. The findings reveal that the singing method significantly enhanced vocabulary recall, retention, and pronunciation, particularly for verbs (fi’il), by acting as a powerful mnemonic device. It dramatically increased student motivation by lowering anxiety and creating an engaging, culturally resonant learning environment that aligns with local Minang traditions. Implementation was feasible and effective, reliant on teacher creativity to adapt songs to the curriculum. This study provides a novel, thick qualitative analysis of the method's application in a pesantren-based MTs, highlighting its utility for teaching grammatical structures and its profound affective benefits.